Clowning and tragic clowning: Miguel de Unamuno as a funny writer - Roberts, Stephen G.H. (Taylor & Francis, 2016)
The present study considers the role and function that humour has in Unamuno’s intellectual and literary universe. It traces Unamuno’s attitude to humour to his reading of the Spanish character in En torno al casticismo (1895) and to his dialogue with the figure of Don Quixote, as found in Vida de Don Quijote y Sancho (1905) and Del sentimiento trágico de la vida (1912). Finally, it looks at the theory of humour offered in the novel Niebla and also at the role that humour played in Unamuno’s later political writings, especially those of exile (1924-1930).